Penerapan Sanksi Hukum Gawal (Kawin Paksa) Dalam Penyelesaian Pelanggaran Kesusilaan Di Kecamatan Tungkal Ulu Kabupaten Tanjung Jabung Barat Jambi - Erdianto Effendi (Jurnal Selat, 2021)
The application of customary criminal sanctions in the Malay community in Tungkal Ulu District in the past was a gawal penalty (forced marriage). Viewed from the aspect of human rights, forced marriage is often considered as a form of human rights violation. Through this research, it is concluded that forced marriage (gawal) in the Tungkal Ulu Malay community does not constitute a violation of human rights because it is carried out on the basis of justification by the local social system and is not something that is against the wishes of the forced partner. Even gawal is basically wanted by the couple